Composite Scaffold of Poly(Vinyl Alcohol) and Interfacial Polyelectrolyte Complexation Fibers for Controlled Biomolecule Delivery - Cutiongco, Marie Francene A.; Choo, Royden K. T.; Shen, Nathaniel J. X.; Chua, Bryan M. X.; Sju, Ervi; Choo, Amanda W. L.; Le Visage, Catherine; Yim, Evelyn K. F. (Frontiers in Bioengineering and Biotechnology, 2015)
Controlled delivery of hydrophilic proteins is an important therapeutic strategy. However, widely used methods for protein delivery suffer from low incorporation efficiency and loss of bioactivity. The versatile interfacial polyelectrolyte complexation (IPC) fibers have the capacity for precise spatiotemporal release and protection of protein, growth factor, and cell bioactivity. Yet its weak mechanical properties limit its application and translation into a viable clinical solution. To overcome this limitation, IPC fibers can be incorporated into polymeric scaffolds such as the biocompatible poly(vinyl alcohol) hydrogel (PVA). Therefore, we explored the use of a composite scaffold of PVA and IPC fibers for controlled biomolecule release. We first observed that the permeability of biomolecules through PVA films were dependent on molecular weight. Next, IPC fibers were incorporated in between layers of PVA to produce PVA–IPC composite scaffolds with different IPC fiber orientation. The composite scaffold demonstrated excellent mechanical properties and efficient biomolecule incorporation. The rate of biomolecule release from PVA–IPC composite grafts exhibited dependence on molecular weight, with lysozyme showing near-linear release for 1 month. Angiogenic factors were also incorporated into the PVA–IPC grafts, as a potential biomedical application of the composite graft. While vascular endothelial growth factor only showed a maximum cumulative release of 3%, the smaller PEGylated-QK peptide showed maximum release of 33%. Notably, the released angiogenic biomolecules induced endothelial cell activity thus indicating retention of bioactivity. We also observed lack of significant macrophage response against PVA–IPC grafts in a rabbit model. Showing permeability, mechanical strength, precise temporal growth factor release, and bioinertness, PVA–IPC fibers composite scaffolds are excellent scaffolds for controlled biomolecule delivery in soft tissue engineering.